ANALISIS RASIO PROFITABILITAS DAN RASIO LIKUIDITAS PADA PT. BANK NEGARA INDONESIA TAHUN 2020-2024 - Delia wati; Rina Malahaytai; Yunita Althin (EKSPOLHUM, 2026)
This study aims to analyze the financial performance of PT. Bank Negara  Indonesia (Persero) Tbk from 2020 to 2024 using financial ratios, including liquidity and profitability ratios. This study assesses the extent to which BNI is able to manage liquidity and generate profits during the economic transition period following the COVID-19 pandemic. The method used is a horizontal analysis of annual financial statements. The results show that BNI experienced a significant increase in profitability performance, demonstrated by increases in Net Profit Margin and Return on Equity during the period. Liquidity ratios also demonstrated stability, reflecting the bank's ability to meet its short-term obligations. Furthermore, there was an increase in operational efficiency and asset quality, supporting profitability growth. In conclusion, BNI demonstrated a significant and stable trend of improving financial performance between 2020 and 2024, although it still needs to maintain efficiency and funding structure to strengthen its performance